2021
DOI: 10.3389/fphar.2021.666368
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Chinese Herbal Injection for Cancer Care: Evidence-Mapping of the Systematic Reviews, Meta-analyses, and Randomized Controlled Trials

Abstract: Background and objective: Cancer is a life-threatening disease worldwide and current standard therapy cannot fulfill all clinical needs. Chinese herbal injections have been widely used for cancer in Chinese and Western hospitals in China. This study aimed to apply evidence mapping in order to provide an overview of the clinical application of Chinese herbal injections in cancer care based on randomized controlled trials, systematic reviews, and meta-analyses.Methods and results: Seven databases were systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…Serving as anticancer CHIs, they are generally accepted in TCM hospitals. Multiple studies in China concluded that different CHIs have similar but uneven positive impacts on cancer patients [ 8 ]. However, the usage of anticancer CHIs has not been unified, which limits the development of these TCM injections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Serving as anticancer CHIs, they are generally accepted in TCM hospitals. Multiple studies in China concluded that different CHIs have similar but uneven positive impacts on cancer patients [ 8 ]. However, the usage of anticancer CHIs has not been unified, which limits the development of these TCM injections.…”
Section: Discussionmentioning
confidence: 99%
“…The Chinese herbal injection (CHI) is based on the theories of traditional Chinese medicine (TCM), and the application of which is a symbol of the modernization of TCM. Currently, over a dozen CHIs are frequently used in treating human cancer: Aidi, Astragalus polysaccharides, Brucea javanica oil emulsion, Cinobufacini, compound matrine, Delisheng, ginseng polysugar, Kangai, Kanglaite, and Shenqifuzheng [ 7 ] The majority studies of these anticancer CHIs are related to lung cancer, and it is concluded that CHIs can reduce ADRs during chemotherapy and promote patients' QOL, which has been demonstrated by evidence-based medicine [ 8 ]. Most of the reports published in English were reviews or meta-analyses, which were based on similar studies previously published in Chinese.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional Chinese medicine (TCM) has been widely used as an adjuvant therapeutic option for cancer treatment (Xiang et al, 2019;Liu S.-H. et al, 2021). High-level clinical studies of TCM injection in cancer care has gradually increased (Yang et al, 2021). Kanglaite injection had been approved by the Chinese State Food and Drug Administration (SFDA) for the treatment of various malignant tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese herbal medicine has received increasing attention. The reason is that Chinese herbs are derived from plants with evidences of high safety and less adverse effects [25,26]. Danshen has been used as a healthy food and as medicine for approximately 1000 years.…”
Section: Discussionmentioning
confidence: 99%